Private enterprise in the developing countries - Zenoff, David B. (Prentice-Hall, 1969)
The book is intended to supplement standard texts on economic developmet, international business management, and public sector policy-making for university students, faculty, and professionals in such disciplines as economic, business administration and public administration.